Hubungan Tingkat Pengetahuan, Dukungan Tenaga Kesehatan dengan Perilaku Pencegahan Luka Ganggren pada Pasien Diabetes Mellitus di Puskesmas Dasuk - Puspitasari, Dian Ika; Damayanti, Cory Nelia (Jurnal Indonesia Sehat, 2023)
Background : Diabetes mellitus is one of the most common diseases in Indonesia. Diabetes mellitus is a disease characterized by an increase in chronic blood sugar levels that can affect many people from all walks of life. One of the risk factors for diabetes mellitus is the level of knowledge, support from health workers, and behavior to prevent gangrene. Purpose:  The purpose of this study was to determine the relationship between the level of knowledge, support from health workers and the behavior of preventing gangrene in patients with diabetes mellitus. Method:  This study uses a type of quantitative research in the form of correlation with a cross sectional research design. the population is teenagers to the elderly aged 20 to > 70 years at the Dasuk Health Center. A sample of 37 people at the Dasuk  Health Center, using a simple random sampling technique. Collecting data using a questionnaire on the level of knowledge, support from health workers and gangrene wound prevention behavior.  The variables studied were the level of knowledge and support of health workers as the dependent variable and the independent variable was gangrene wound prevention behavior. Analysis of the data used is statistical test Spearmen rho correlation. Result: The results showed that almost half of the diabetes mellitus patients at the Dasuk Health Center had 25 levels of knowledge with gangrene wound prevention behavior, while the support of health workers with gangrene wound prevention behavior was 21. The results of statistical test analysis using Spearman correlation showed p = 0.000 known that p < (0.05). Conclusion: there is a relationship between the level of knowledge, support from health workers and the behavior of preventing gangrene from diabetes mellitus patients. The researcher's suggestion should be for the puskesmas to further increase the provision of in-depth information to patients about the prevention of diabetes mellitus as one of the successes of diabetes mellitus therapy.